Decline in lichen biodiversity on oak trunks due to urbanization. (20th February 2014) - Lättman, Håkan; Bergman, Karl‐Olof; Rapp, Malin; Tälle, Malin; Westerberg, Lars; Milberg, Per
<x xml:space="preserve">Abstract</x> Biodiversity often suffers from urbanization. In the present study, we focused on how the duration of urbanization affects the richness of 17 epiphytic lichen species and their cover on large oaks in urban environments in a city of 100 000 inhabitants in southeast Sweden. We also surveyed trees in adjacent rural areas, selected to have similar distributions of tree trunk circumference and surrounding oak density (within 300 m). Lichen richness and cover were lower on urban trees compared to rural trees. Furthermore, richness and cover decreased with the length of time that urban trees had been surrounded by houses. Most of the species that were analysed demonstrated a decline in occurrence with respect to the duration of housing development. The reduction in the probability of occurrence varied from 60% (Calicium viride, Evernia prunastri), 80% (Chrysothrix candelaris) to 90% (Ramalina spp.) during the considered 160‐year period of urbanization. Therefore, even if valuable trees survive over the course of development, their lichen biota is likely to become depleted over time.